AB0352 Diabetes Mellitus in Patients with Rheumatoid Arthritis. (9th June 2015) - Kostoglou-Athanassiou, I.; Tzanavari, A.; Katsavouni, C.; Kalaycheva, N.; Banti, T.; Athanassiou, P.
Abstract : Background: In rheumatoid arthritis (RA) glucose metabolism may be affected either by the autoimmune inflammatory disease itself, or by the treatment used to manage the disease. Metabolic syndrome seems to be prevalent in RA patients. Objectives: The aim was to study the prevalence of diabetes mellitus type 2 and metabolic factors related to the development of atherosclerosis within a cohort of RA patients cared for within a single rheumatology department. Methods: Within a cohort of 204 RA patients, aged 29-88 (mean ± SEM) 62.87±08.86 years the incidence of diabetes mellitus and metabolic factors related to the development of atherosclerosis was studied. In the cohort of RA patients ESR was 37.12±1.57 mm/h, CRP 1.56±0.15 mg/dl and the disease activity index DAS28 was 3.80±0.13, 49% being positive for rheumatoid factor and 23% having positive anti-CCP antibodies. Results: Within the cohort of 204 RA patients 45 (22.06%) were found to suffer from diabetes mellitus type 2, 5 being on therapy with a combination of insulin and oral antidiabetic agents, 10 on oral antidiabetic agents, and the rest on diet only. Within the cohort of RA patients morning glucose concentration was 110±2.6 mg/dl (mean ± SEM), cholesterol concentration 200.3±2.98 mg/dl, HDL cholesterol 55.64±1.18 mg/dl, LDL cholesterol 123.19±2.41 mg/dl and triglyceride 125.4±3.7 mg/dl. Within the cohort of RA patients 33 had hyperlipidemia requiring therapy with lipid lowering agents, mainly statins and in 2 cases a combination of statin and fenofibrate. Conclusions: Diabetes mellitus type 2 seems to be prevalent amongst patients with RA, hyperlipidemia being also prevalent. The disease itself, which is related to an autoimmune inflammatory process and the medications required for its management may affect blood glucose metabolism adversely. References: Straub RH. Insulin resistance, selfish brain, and selfish immune system: an evolutionarily positively selected program used in chronic inflammatory diseases. Arthritis Res Ther 2014;16 (Suppl 2):S4. Jiang P, Li H, Li X. Diabetes mellitus risk factors in rheumatoid arthritis: a systematic review and meta-analysis. Clin Exp Rheumatol 2014 [Epub ahead of print]. Disclosure of Interest: None declared